Marketing digital: influência na decisão de compra dos discentes da Universidade Federal do Amazonas - Santos, Isabele dos Santos (Brasil, 2024)
Digital marketing has become essential in the social and organizational environment, enabling several opportunities, being decisive for interacting with and attracting consumers, seeking data about them, ensuring satisfaction, influencing purchases and recurrence. The objective of this research was to analyze the influence of digital marketing on the purchasing decisions of students from the Federal University of Amazonas, aged 18 to 50. The research methodology used a quantitative approach with the application of a questionnaire, whose sample was non-probabilistic, composed of students who made online purchases. The results of the research indicated that digital marketing influences the purchasing decisions of students, through online reviews and profiles of stores and influencers on social media. It highlighted decision-making, with a predominance of students who make online purchases between 1 and 2 times per month, influenced by comments, products and services seen through social networks and online advertisements, highlighting the importance of the tool most used by digital marketing. This study concludes that students feel more confident in purchasing products or services that have some type of evaluation or opinions from other consumers or influencers on social media, with social networks being the most influential platform in their purchasing decisions.